Errors and Action Monitoring: Errare Humanum Est Sed Corrigere Possibile - Vidal, Franck; Burle, Boris; Hasbroucq, Thierry (Frontiers in Human Neuroscience, 2020)
It has been recognized long ago by Seneca through his famous “errare humanum est.” that the human information processing system is intrinsically fallible. What is newer is the fact that, at least in sensorimotor information processing realized under time pressure, errors are largely dealt with by several (psycho)physiological specific mechanisms: prevention, detection, inhibition, correction and, if these mechanisms finally fail, strategic behavioural adjustments after errors. In this article we will review several datasets from laboratory experiments showing that the human information processing system is well equipped not only to detect and correct errors when they occur but also to detect, inhibit and correct them even before they fully develop. We will argue that, these (psycho)physiological mechanisms are important to consider when the brain works in everyday settings in order to render work systems more resilient to human errors and, hence, safer.